2006
DOI: 10.1158/0008-5472.can-05-4654
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Clinical Significance of Circulating Endothelial Progenitor Cells in Human Non–Small Cell Lung Cancer

Abstract: Until recently, it was generally accepted that vascularization of tumors arises exclusively from endothelial sprouting. Whether circulating bone marrow-derived endothelial progenitor cells (EPC) participate in the progression of non-small cell lung cancer (NSCLC) has not yet been evaluated. EPCs labeled with CD34, CD133, and vascular endothelial growth factor receptor-2 (VEGFR2) antibodies were counted by flow cytometry in the peripheral blood of 53 NSCLC patients. Furthermore, by means of a quantitative reve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
144
2
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 167 publications
(153 citation statements)
references
References 38 publications
6
144
2
1
Order By: Relevance
“…It is noteworthy that several reports have suggested that CECs and EPCs are increased in patients with cancer and are correlated with a more aggressive disease course. [2][3][4] Overall, these findings suggest that CECs may be related to the so-called angiogenic switch, a phenomenon that characterizes the shift to a more aggressive course of the disease, and support the idea that, in CLL, CECs may represent a new and easy-to-use prognostic marker to be tested in large multicenter series of patients for correlation with prognosis. It remains to be determined whether, in patients with CLL, CECs can be used as a surrogate marker to monitor the efficacy of therapy and whether patients with high CEC levels may represent a subset of patients who are eligible for antiangiogenic treatments, including new drugs like lenalidomide.…”
Section: Discussionsupporting
confidence: 65%
“…It is noteworthy that several reports have suggested that CECs and EPCs are increased in patients with cancer and are correlated with a more aggressive disease course. [2][3][4] Overall, these findings suggest that CECs may be related to the so-called angiogenic switch, a phenomenon that characterizes the shift to a more aggressive course of the disease, and support the idea that, in CLL, CECs may represent a new and easy-to-use prognostic marker to be tested in large multicenter series of patients for correlation with prognosis. It remains to be determined whether, in patients with CLL, CECs can be used as a surrogate marker to monitor the efficacy of therapy and whether patients with high CEC levels may represent a subset of patients who are eligible for antiangiogenic treatments, including new drugs like lenalidomide.…”
Section: Discussionsupporting
confidence: 65%
“…In addition, analysis of the relation between IL-17A and MVD in Accumulating evidence has revealed that bone marrow-derived EPCs are involved in the process of vasculogenesis in physiological or pathological neovascularization. Dome et al (25) found that the levels of bone marrow-derived EPCs significantly increased in patients with non-small-cell lung cancer and were arrested in small intratumoral capillaries or located in the capillary walls. Asosingh et al (18) demonstrated that circulating EPCs were increased in asthma patients and were related to the increased numbers of submucosal vessels.…”
Section: Discussionmentioning
confidence: 99%
“…In cancer patients, the number of circulating EPCs is increased. [12][13][14] Importantly, in various animal tumor models, transplanted EPCs incorporated functionally into tumor-associated vessels. Following transplantation of marked bone marrow into tumorbearing mice, marked cells were found in the neovasculature of the developing tumors.…”
Section: Epcs In Tumor Angiogenesismentioning
confidence: 99%